Financial Inclusion in Latin America and the Caribbean: Review and Lessons - Ricardo N. Bebczuk (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2008)
Our study critically surveys financial inclusion in Latin American and Caribbean countries, gauging access to both credit and deposit accounts by poor households. Our review confirms some pieces of conventional wisdom in this area, but challenges some others. Regarding the latter, we claim that (a) Limited financial inclusion does not simply follows from unfair discrimination against the poor, but to a great deal from a low demand for financial services and scarce access for the population at large. In this sense, we argue that supply-side constraints have a second-order importance; (b) Despite the impressive progress of microfinance in recent years, stakeholders should avoid overoptimism, rooted in an apparent over-advertisement of a few successful cases. While a potentially powerful tool to fight poverty, microcredit must be carefully targeted, and granted by highly specialized intermediaries under commercially-oriented criteria; (c) Although financial inclusion is a social matter, the private sector has provided more and better responses than the public sector. Furthermore, these private programs have proven to be quite profitable; (d) Recent experiences in several LAC countries hint that governments can play a decisive role in coordinating financial inclusion initiatives, leading normative changes, and supporting innovative banking outreach strategies without engaging directly in credit allocation; and (e) Governments, donors and intermediaries should make coordinated efforts to assemble microdata and encourage sound impact evaluations comparable across countries and time. A number of policy recommendations emerge from the analysis.
Keywords: 330; Armut; Bankgeschäft; Mikrofinanzierung; Lateinamerika; Karibische Staaten